This forum s for all - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The electronic conference to prepare the European Forum on Rural Development Cooperation (Montpellier, France, September 2002) was set for launch on 20 July 2002. Discussions in French and English, open to all interested parties, cover...